Relevansi Kesadaran Global terhadap Produk Halal Hubungannya dengan Perilaku Ekonomi Masyarakat Indonesia di Era Revolusi Industri 4.0 - Ahyani, Hisam; Putra, Haris Maiza; Muharir, Muharir; Mutmainah, Naeli; Prakasa, Armelia (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2023)
Global Awareness of Halal Products in Relation to the Economic Behavior of the Indonesian Society in the Industrial Revolution 4.0 Era, nowadays it has become a demand of the times whose cause is the existence of a great opportunity for the existence and development of the halal industry (sharia economy) in Indonesia. Where an indicator of awareness of halal products in Indonesia is the behavior of consumers or non-Muslim communities in consuming halal products. This library research was obtained from various primary and secondary sources from various literacy such as books, journals and the internet. The results of the study prove that the relevance of global awareness of halal products is related to the economic behavior of the Indonesian people in the era of the industrial revolution 4.0 as it is today, as evidenced by the many potential attractions of halal food in Indonesia which have their own variants in meeting market demand for halal products so that Indonesia as a The largest Muslim population in the world should be aware of their behavior in consuming halal products on the market, meaning that they are not inferior to non-Muslims in developing these halal products. Equally important in forming global awareness of halal products, the economic behavior of the Indonesian people, especially in this all-digital era (4.0), should carry out halal labeling and halal certification in order to be able to compete with market share.